Analisis Tingkat Kepuasan dan Loyalitas Konsumen Lotu Coffee and Eatery di Jalan Kalimantan Kota Bandung - Gloria, Jeanete Gwendelin; Pardian, Pandi; Hapsari, Hepi; harina, Anne (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The coffee business sector is now experiencing a significant increase in Bandung City. This increase cannot be separated from the increasing intersert and consumption of coffee among Indonesians. Coffee consumption in Indonesia has increased rapidly in recent years. This is driven by various factors such as lifestyle changes, the growth of the middle class and the increasing popularity of coffee shops as places to gather and socialize. One of the main strategies to deal with increasingly fierce business need to make various efforts to identify consumer preferences ranging from the desired quality and flavour of coffee to convenience and griendly effiecient service. One of the coffee business in Bandung is Lotu Coffee and Eatery. Consumer expectations and satisfaction are measured using Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Consumer satisfaction can lead to consumer loyalty to the products sold, therefore consumer loyalty in this study is measured using the Customer Loyalty Index (CLI). Data collection was carried out by distributing 100 questionnaires and showed that consumers were very satisfied and had a high level of loyalty.